DEVELOPMENT OF STUDENT ACTIVITY SHEET BASED ON SCIENTIFIC APPROACH TO IMPROVE PROBLEM SOLVING SKILL OF SURROUNDING ENVIRONMENT IN ELEMENTARY SCHOOL STUDENTS - Widodo, Slamet (JURNAL PENDIDIKAN ILMU SOSIAL, 2017)
This study aims to design and develop the feasibility of scientific approach-based students’ worksheet to improve four graders’ problem-solving skills on surrounding environment issues. This study was conducted using Research and Development (RD) method which produces scientific approach-based students’ worksheet. Practicality of this students’ worksheet based on learning practice showed excellent result. This scientific approach-based students’ worksheet can be used to teach and improve students’ problem-solving skills on surrounding environment in the fourth grade of Elementary School. This case is proved by good performance of students in solving problems related to their surrounding environment with a percentage of 81% which shows very high category.